Health, wealth & workforce exit: Disability insurance & individual accounts - Jason S. Seligman (W.E. Upjohn Institute for Employment Research, 2005)
Current debate on the Social Security Administrations long-term finance of benefits includes proposals for independent private investment via individual accounts. The author first investigates what implications disability might have for equity savings account balances. In light of results, incentives to exit the workforce ahead of retirement age are considered when a defined benefit program for disability insurance continues to be available. Included simulation uses historic wage series, equity market performance, and current OASDI regulations for cohorts retiring over the period of 1929 - 2003.
Keywords: 330; Erwerbsunfähigkeit; Erwerbsunfähigkeitsrente; Altersgrenze; Private Rentenversicherung; Kapitaldeckungsverfahren; Simulation; USA